PENGARUH PERMAINAN TRADISIONAL ENGKLEK TERHADAP PERKEMBANGAN FISIK MOTORIK KASAR ANAK USIA 5-6 TAHUN - Raihana Raihana; Budiyah Febria Sari (UIR PRESS, 2021)
This research aimed to know the influence of traditional game engklek on children’s rude motoric physic development in 5 -6 years old at Puri air dingin resident RT. 03 Pekanbaru. This research used experimental research with one group pretest-posttest design, quantitative approach. The population in this research took 11 children in 5 – 6 years old at Puri air dingin resident RT. 03 Pekanbaru. Meanwhile, the data collection technique used a non-test instrument or performance test. The data analysis technique in this research used a non-parametric statistical method with Wilcoxon signed ranks test. The hypothesis result in this research could be seen from Asymp. Sig. (2-tailed) in score 0.03. in case, 0.03 < 0.05, it could be concluded that Ha was accepted. Also, it could be stated that average of the children’s rude motoric physis development in 5 – years old by using engklek traditional game gave influence in it. Therefore, traditional game engklek gave influence of children’s rude motoric physic development in 5 -6 years old at Puri Air Dingin Resident RT.